Trade liberalization and poverty in the Middle East and North Africa - Minot, Nicholas; Chemingui, Mohamed Abdelbasset; Thomas, Marcelle; Dewina, Reno; Orden, David (International Food Policy Research Institute, 2010)
This report examines the impact of trade liberalization on non-oil-exporting countries of the Middle East and North Africa (MENA), with particular emphasis on its impact on the poor. First the report describes the basic characteristics related to agriculture, trade, and poverty for eight MENA countries and reviews previous studies examining the impact of trade liberalization on these countries. The eight are the developing countries in the MENA region that are not major oil exporters: Djibouti, Egypt, Jordan, Lebanon, Morocco, Syria, Tunisia, and the West Bank and Gaza.1 Second, the report uses household survey data and computable general equilibrium models to simulate the effect of trade liberalization on low-income households in four of these countries: Egypt, Tunisia, Syria, and Morocco.